Maternal and neonatal group B streptococcus colonisation: A systematic review and the meta-analysis of matched-pair studies - Lee, Kai Wei; Yap, Sook Fan; Murdan, Sudaxshina; Zainudin, Zurina; Abdul Hamid, Habibah; Emamjomeh, Mohsen; Mohd Desa, Mohd Nasir; Sither Joseph, Narcisse Mary; Azmai Amal, Mohammad Noor; Amin‐Nordin, Syafinaz (John Wiley and Sons Inc, 2024)
Aim: To determine the prevalence of group B Streptococcus (GBS) carriage among parturient women and neonates, and the relative risk of vertical transmission, the relative risk of early and late-onset GBS and the pooled incidence of early-late-onset GBS infection. Methods: A systematic search of relevant cohort studies from three electronic databases to identify all relevant studies published up to 7 November 2022. The review was conducted in accordance with PRISMA guidelines. Estimates were pooled using random-effects meta-analyses. Results: A total of 54 articles with 355 787 matched pairs of parturient women and neonates from 30 countries were included in the analysis. The pooled prevalence of GBS colonisation was 17.1% among the pregnant women and 1.0% among neonates. The pooled prevalence of vertical transmission of GBS was 4.5% and the pooled relative risk of GBS colonisation of neonates born to mothers with GBS was 9.9. Conclusion: We support the implementation of targeted intrapartum antibiotic prophylaxis for all women who are positive for GBS as well as women with risks factors for early onset GBS in their infants regardless of their GBS colonisation status.